2021
DOI: 10.1111/tpj.15429
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxins m are major players in the multifaceted light‐adaptive response in Arabidopsis thaliana

Abstract: SUMMARY Thioredoxins (TRXs) are well‐known redox signalling players, which carry out post‐translational modifications in target proteins. Chloroplast TRXs are divided into different types and have central roles in light energy uptake and the regulation of primary metabolism. The isoforms TRX m1, m2, and m4 from Arabidopsis thaliana are considered functionally related. Knowing their key position in the hub of plant metabolism, we hypothesized that the impairment of the TRX m signalling would not only have harmf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Anthocyanins are pigmented flavonoids, with sugars at position three or sometimes in another position [ 122 ]. Their HL-induced accumulation was demonstrated in Arabidopsis , and this change was redox-associated based on its fine-tuning by isoforms of TRX [ 232 ]. A further relationship of anthocyanins with the redox system is indicated by their antioxidative properties and role in the tolerance to abiotic stress-induced oxidative stress [ 233 ].…”
Section: Light Intensity- and Spectrum-associated Adjustment Of Metab...mentioning
confidence: 99%
“…Anthocyanins are pigmented flavonoids, with sugars at position three or sometimes in another position [ 122 ]. Their HL-induced accumulation was demonstrated in Arabidopsis , and this change was redox-associated based on its fine-tuning by isoforms of TRX [ 232 ]. A further relationship of anthocyanins with the redox system is indicated by their antioxidative properties and role in the tolerance to abiotic stress-induced oxidative stress [ 233 ].…”
Section: Light Intensity- and Spectrum-associated Adjustment Of Metab...mentioning
confidence: 99%
“…Wild type lines (ecotypes Columbia-0 (Col0) and Landsberg erecta (Ler)) and TRX-defective mutants trxf1 , trxf2 , trxm1 , trxm2 , trxm4 (genetic background Col0) and trxm3 (genetic background Ler) [ 12 , 21 ] of A. thaliana were grown in 0.5× MS medium supplemented with 0.5% sucrose containing 0.8% agarose for root analyses (for confocal and light microscopy analyses and Western blotting assays). In vitro plants were cultured in a growth chamber at 22 °C/21 °C (light/dark) under long-day conditions (16-h-light/8-h-dark) and with a photosynthetically active radiation of 100 µmol photons m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…TRX f proteins are of eukaryotic origin, whereas m -type TRXs are of prokaryotic origin [ 7 ]. Several studies have indicated a wide range of different functions in plant processes [ 8 , 9 , 10 , 11 , 12 ], and it is not evident whether TRX diversity suggests functional redundancy or specificity for target proteins in plants. It has been known for several years that chloroplast TRXs regulate processes such as starch metabolism, oxidative stress response, lipid biosynthesis, nitrogen metabolism, protein folding, and translation [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…NPQ has different components: qE (energy-dependent quenching), qZ (zeaxanthin-dependent quenching), qT (state-transition quenching), qI (photo-inhibitory quenching) and qH (sustained and slowly reversible quenching) [ 80 , 81 , 82 ]. Behind all these photoprotective mechanisms, there is a dynamic redox network in which TRXs play active roles [ 28 ]. It follows now a discussion of the relevance of TRXs in the regulation of the different NPQ components ( Figure 2 ).…”
Section: Redox Regulation Of Non-photochemical Quenchingmentioning
confidence: 99%
“…Usually, this PTM has important effects on protein conformation, activity and even stability, hence becoming a dynamic regulatory mechanism in some proteins that can switch between two redox states (thiol/disulphide) or form multiprotein complexes [ 22 , 23 , 24 ]. Some members of the chloroplast thioredoxin (TRX) family were reported to be key players in the redox regulation of light-dependent processes [ 25 , 26 , 27 , 28 ]. TRXs are redox signalling proteins with an active site containing two Cys separated by two amino acid residues (CXXC).…”
Section: Introductionmentioning
confidence: 99%